The elasticity of taxable income: A meta-regression analysis - Carina Neisser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
The elasticities of taxable (ETI) and broad income (EBI) are key parameters in optimal tax and welfare analysis. To examine the large variation in estimates found in the literature, I conduct a comprehensive meta-regression analysis of elasticities that measure behavioral responses to income taxation using information from 51 different studies containing 1,420 estimates. I find that heterogeneity in reported estimates is driven by regression techniques, sample restrictions and variations across countries and time. Moreover, I provide descriptive evidence of the correlation between contextual factors and the magnitude of an elasticity estimate. Overall, the study confirms the fact that the ETI itself is endogenous to the underlying tax system. I also document that selective reporting bias is prevalent in the literature. The direction of reporting bias depends on whether or not deductions are included in the tax base.
urn:nbn:de:bsz:180-madoc-435600
Keywords: C81; H24; H26; 330; elasticity of taxable income; income tax; behavioral response; meta-regression analysis